Identification of CD24 as a marker of Patched1 deleted medulloblastoma-initiating neural progenitor cells - Robson, Jonathan P.; Kool, Marcel; Korshunov, Andrey; Pfister, Stefan (PLOS ONE, 2019)
High morbidity and mortality are common traits of malignant tumours and identification of the cells responsible is a focus of on-going research. Many studies are now reporting the use of antibodies specific to Clusters of Differentiation (CD) cell surface antigens to identify tumour-initiating cell (TIC) populations in neural tumours. Medulloblastoma is one of the most common malignant brain tumours in children and despite a considerable amount of research investigating this tumour, the identity of the TICs, and the means by which such cells can be targeted remain largely unknown. Current prognostication and stratification of medulloblastoma using clinical factors, histology and genetic profiling have classified this tumour into four main subgroups: WNT, Sonic hedgehog (SHH), Group 3 and Group 4. Of these subgroups, SHH remains one of the most studied tumour groups due to the ability to model medulloblastoma formation through targeted deletion of the Shh pathway inhibitor Patched1 (Ptch1). Here we sought to utilise CD antibody expression to identify and isolate TIC populations in Ptch1 deleted medulloblastoma, and determine if these antibodies can help classify the identity of human medulloblastoma subgroups. Using a fluorescence-activated cell sorted (FACS) CD antibody panel, we identified CD24 as a marker of TICs in Ptch1 deleted medulloblastoma. CD24 expression was not correlated with markers of astrocytes or oligodendrocytes, but co-labelled with markers of neural progenitor cells. In conjunction with CD15, proliferating CD24+/CD15+ granule cell precursors (GCPs) were identified as a TIC population in Ptch1 deleted medulloblastoma. On human medulloblastoma, CD24 was found to be highly expressed on Group 3, Group 4 and SHH subgroups compared with the WNT subgroup, which was predominantly positive for CD15, suggesting CD24 is an important marker of non-WNT medulloblastoma initiating cells and a potential therapeutic target in human medulloblastoma. This study reports the use of CD24 and CD15 to isolate a GCP-like TIC population in Ptch1 deleted medulloblastoma, and suggests CD24 expression as a marker to help stratify human WNT tumours from other medulloblastoma subgroups.